2022
DOI: 10.1177/21582440221131242
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present and Future of FinTech Research: A Bibliometric Analysis

Abstract: This study has conducted a meta-literature review examining the past, present and possible future trends of Fintech research using 360 selected articles published between 2006 and June 2020. Both quantitative and qualitative techniques were applied. In the quantitative approach, a bibliometric citation analysis using HistCite and VOSviewer software was conducted and the qualitative analysis covered the identification of four main research streams related to (i) Bitcoin and digital currency, (ii) crowdfunding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 97 publications
(117 reference statements)
0
12
0
1
Order By: Relevance
“…The financial industries and regulators like Saudi Arabian Monetary Agency (SAMA) used FinTech for financial regulatory activities. Currently, FinTech and RegTech are used to optimize and analyze large volume of data to understand dynamic behavioral patent of users (Bajwa et al , 2022). Furthermore, the RegTech is used to detect and prevent financial crimes and meet due diligence requirements (Northern Trust, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The financial industries and regulators like Saudi Arabian Monetary Agency (SAMA) used FinTech for financial regulatory activities. Currently, FinTech and RegTech are used to optimize and analyze large volume of data to understand dynamic behavioral patent of users (Bajwa et al , 2022). Furthermore, the RegTech is used to detect and prevent financial crimes and meet due diligence requirements (Northern Trust, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In spite of the rapid growth of academic papers on FinTech since 2015, literature review studies remain few (Dosso & Aysan, 2022;Takeda & Ito, 2021). The majority of current quantitative literature reviews have concentrated on highlighting the most in uential elements of the FinTech literature, including the leading articles, authors, sources, institutions, and countries (Bajwa et al, 2022;Li & Xu, 2021). Thematic analyses with further research trends and conversations investigations are rear (Bhatt et al, 2022;Varma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Secinaro et al (2021) used bibliometric and coding analysis and they believe that the relationship between Blockchain and accountability has not yet been clear and validated and found that Blockchain is a promising and multidisciplinary field comprised of scholars, and qualitative research, particularly discourse analysis, is the most popular method among authors. Bajwa et al (2022) examined 360 FinTech articles published between 2006 and 2020, categorized them into four research categories, highlighted the top countries, organizations, journals, authors and articles and made recommendations for future research. However, Pizzi et al (2021) focused on performing a bibliometric analysis of managerial auditing response to digital transformation and found four distinct research areas, including technological innovation, continuous auditing, fraud detection and data analytics, whereas Alex et al (2022) used the Proknow-C methodology and the Scopus database to conduct a bibliometric and systemic analysis of the academic literature on blockchain in accounting and auditing and noted that relevant journals and authors who all highlighted the disruptive potential of blockchain in improving the transparency and standard of financial and sustainability reports in corporations.…”
Section: Introductionmentioning
confidence: 99%